Research Champions: mixed methods evaluation of an interdisciplinary programme for community nurses and allied health professionals to build research capacity - Abrahamson, Vanessa; Baldock, Bethany; Tomlinson, Lee; Jackson, Carrie; Manley, Kim; Wilson, Patricia (Advanced Journal of Professional Practice, 2023)
Aims: to evaluate the Research Champions programme and learn what practitioners perceived as key challenges/benefits; to identify measurable outcomes; and to identify ways of increasing programme uptake. Background: research within healthcare services is a priority, highlighted throughout UK policy and reflected internationally. The one-year programme was designed to enable nurses, midwives and allied health professionals to develop their practice by learning about research as part of practice development. Design: mixed methods longitudinal: questionnaires/focus groups with practitioners and their managers. Methods: Practitioners in three cohorts (2018-21) were asked to complete baseline and post-programme questionnaires; managers were asked to complete post-programme questionnaires; practitioners in the third cohort participated in focus groups. The research facilitator tracked practitioners’ progress for evidence of measurable outcomes. Qualitative data was analysed thematically, underpinned by a realist approach, with strategies to maximise rigour. Reporting complies with the COREQ qualitative checklist. Results: Twenty-seven (of 31) practitioners completed the pre-programme questionnaire, 19 the post-programme questionnaire; and 13 (of 29) managers completed their questionnaire. Measurable outcomes included Masters degree, research internships, conference presentations, further research projects and promotion. Nine practitioners participated in two focus groups. Three themes were identified. Aspirations and challenges reflected tension between wanting to develop their professional practice using research while negotiating barriers. Coming together, learning together concerned the importance of time to reflect and develop research knowledge/skills, alongside developing confidence to innovate practice. Moving forward, maximising impact evidenced how the programme was a steppingstone to further professional and service development and transforming culture. Conclusion: Practitioners’ aspirations spanned individual, service and organisational goals. This introductory programme provided the first step to further clinical-academic opportunities for the most capable and motivated practitioners. Key mechanisms included developing research knowledge/skills and the confidence to translate learning into practice. Immediate gains included practitioners sharing their knowledge, skills and enthusiasm for research with colleagues. Medium to longer term gains included changes in clinical practice with direct patient benefit, developing a research network, ongoing research activities and embarking on a clinical-academic pathway.